Characteristics of myoglobin degradation by cold plasma and its pro-oxidative activity on lipid in washed fish muscle. (30th September 2022) - Ke, Zhigang; Bai, Yiwen; Zhu, Hao; Xiang, Xingwei; Liu, Shulai; Zhou, Xuxia; Ding, Yuting
Graphic abstract: Highlights: CP treatment caused heme degradation in Mb both in solution and in fish muscle. Heme degradation products in Mb upon CP treatment induced fish lipid oxidation. Typical lipid oxidation products including aldehydes, ketones, alcohols etc. were produced. Abstract: In this study, the degradation of myoglobin both in solution and in tuna muscle by cold plasma (CP) was investigated through ultraviolet–visible and fluorescence spectroscopy analysis, and the effect of the degradation products on lipid oxidation in washed turbot muscle (WTM) was explored. Results showed that heme in myoglobin was degraded upon CP treatment, from which a fluorescent product was formed and iron was released. The degradation products promoted lipid oxidation in WTM during cold storage, in which the released iron played an important role. Results of gas chromatography-ion mobility spectrometry analysis showed that the contents of 37 volatile compounds in WTM were increased by heme degradation products induced lipid oxidation, including 20 aldehydes, 9 alcohols, 5 ketones and 3 furans. This study provides a new insight to the mechanism of lipid oxidation in CP-treated fish during cold storage, as well as guidance for preserving myoglobin-containing foods with CP.